PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN BRAIN BASED LEARNINGUNTUK MENINGKATKAN KEMAMPUAN PROSEDURAL DAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X MADRASAH ALIYAH - Suganda, Anton Tirta (2012)
These research aimed to increase of students mathematical procedural ability and conceptual understanding with Brain-Based Learning approach. These experimental research design was non-equivalent control group. Experimental class getting Brain-Based Learning approach while control class getting conventional learning. The data were gathered from instruments such as mathematical procedural ability and conceptual understanding, student attitude scale, and observation sheets. The population of these research was the teen grade students of Madrasah Aliyah in west Java. By taking a sample of two classes as an experimental class and control class by purposive sampling. The data were analyzed quantitatively and qualitatively. Quantitative analysis performed over the test results, t-test were to test different mean of the two classes. The qualitative analysis was conducted to examine student activities, student attitudes, and teacher opinions towards learning that has been done. Analysis results showed that mathematical procedural ability by Brain-based Learning approach was increase better than by conventional learning and conceptual understanding as well as. Positive attitude aimed towards Brain-Based Learning by students. Brain-based Learning approach show enthusiasm, liveliness and students involvement during the learning progress.